DAYA HAMBAT EKSTRAK DAUN CEMCEM (Spondias pinnata (L.f) Kurz.) TERHADAP PERTUMBUHAN Escherichia coli ATCC 8739 SECARA IN VITRO - Rini Trisnawati, Nyoman; Ari Sandhi W., Putu; Sugitha, I Made (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 5 No 2 (2016): Jurnal ITEPA)
The objective of this study is to determine the inhibition of cemcem leaf extract ( Spondias pinnata (L.f) Kurz.) to the growth of Escherichia coli ATCC 8739 in vitro and to observe the type of antibacterial compounds contained in the cemcem leaf extract. This research uses a experimental method with five treatments concentration of cemcem leaf extract that is 10%, 20%, 30%, 40% and 50%. The results of experiment were presented in tables and pictures. Data were analyzed by descriptive statistic. The results showed that the cemcem leaf extract could inhibit the growth of Escherichia coli ATCC 8739 with the highest inhibition at 40% concentration (4.62 ± 1.0953 mm) and cemcem leaf extract contain antibacterial compounds such as flavonoid, tanin and saponin.
Keywords: cemcem leaf extract, Escherichia coli ATCC 8739, inhibition, antibacterial compounds